Physiological responses of wild antelope to exercise training as a prospective treatment to prevent capture myopathy - Breed, Dorothy (Department of Human Biology, 2023)
Capture myopathy is a lethal condition associated with physiological stress in wildlife and is responsible for most deaths during game capture. Exercise training to improve fitness has been proposed as a preventative management strategy for capture myopathy but lacks scientific evidence. The aim of this study was to determine whether regular exercise training of wild antelope is indeed feasible, and whether physiological adaptations occur that could mitigate the response to capture stress. Forty wild blesbok (Damaliscus pygargus phillipsi) were habituated for two weeks to a boma. Twenty were randomly selected to be exercise trained for four weeks, consisting of thirtyminute low, medium and high intensity running sessions four or five times per week. Ten of the exercise trained and ten untrained blesbok were subjected to a twenty-minute capture stress event that included chasing by humans, a motorised quadbike, and a helicopter. Immediately following this event, the animals were immobilised, physiological variables recorded, and blood samples obtained at 0 and 40 minutes. The same sampling occurred on days 2 and 5 after the original stress event but only at 0 minutes. Untrained and unstressed animals served as controls for the effect of training and the acute stress response, respectively. The exercise trained blesbok responded physiologically better to the capture stress event , indicated by lower blood lactate concentrations [exercised: Median (Mdn) = 9.4 mmol/l , Interquartile range (IQR) = 7.9 – 12.4 mmol/l vs. non-exercised: Mdn = 11.0 mmol/l, IQR = 10.5 – 14.1 mmol/l] and reduced post-capture stress rectal temperatures [exercised: Mdn = 41.4 °C, IQR = 41.1 – 41.6 °C vs. non-exercised: Mdn: 41.8 °C, IQR = 41.6 - 41.8 °C]. Although the pH did not differ between the groups - the exercise trained blesbok group had less animals presenting acidaemic, there was an increased cHCO3 - [mean (M) ± standard deviation (SD) of exercised: 20 ± 3 vs. non-exercised: 16 ± 5 mmol/l) and BEecf (M ± SD of exercised: - 5 ± 3 vs. non-exercised: - 10 ± 6 mEq/L) that supports an increased buffering ability for the exercised group. These findings conform to previous exercise training studies in humans, horses, and rodents that indicate similar adaptations in trained groups exposed to exertional stress compared to untrained groups. The data also confirmed the severe hypoxaemia that is caused by the opioid immobilisation drugs. This is the first study showing that wild antelope can be successfully exercise trained, which led to physiological adaptations resulting in improved fitness. Whether this training programme will prevent the onset of capture myopathy and reduce fatalities still needs to be further investigated.